2019
DOI: 10.12659/msm.916835
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic Acid Shows Anti-Proliferative Effects on Non-Small Cell Lung Cancer (NSCLC) Cells by Activating Reactive Oxygen Species (ROS)-Induced Endoplasmic Reticulum (ER) Stress-Mediated Apoptosis

Abstract: Background Gambogic acid (AG) is believed to be a potent anti-cancer agent. ER (endoplasmic reticulum) stress-induced cell apoptosis was identified as one of the anti-proliferative mechanisms of several anti-cancer agents. In this study, we investigated the involvement of ER stress-induced apoptosis in the anti-proliferative effect of GA on NSCLC (non-small cell lung cancer) cells. Material/Methods GA at 0, 0.5, and 1.0 μmol/l was used to treat A549 cells. We also used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…It also induces oxidative stress-dependent caspase activation to mediate apoptosis in human bladder cancer T24 and UMUC3 cells [652]. Moreover, GA increases the expressions of ER stress markers such as GRP78, CHOP, activating transcription factor 6 (ATF-6) and caspase-12, and co-treatment with chemical chaperone, 4-PBA, significantly reduces these expressions and apoptosis in human NSCLC A549 cells, so it is suggested that GA induces ER stress to mediate apoptosis [659].…”
Section: Gambogic Acid (Ga)mentioning
confidence: 98%
“…It also induces oxidative stress-dependent caspase activation to mediate apoptosis in human bladder cancer T24 and UMUC3 cells [652]. Moreover, GA increases the expressions of ER stress markers such as GRP78, CHOP, activating transcription factor 6 (ATF-6) and caspase-12, and co-treatment with chemical chaperone, 4-PBA, significantly reduces these expressions and apoptosis in human NSCLC A549 cells, so it is suggested that GA induces ER stress to mediate apoptosis [659].…”
Section: Gambogic Acid (Ga)mentioning
confidence: 98%
“…In addition, ER stress has been reported to be closely associated with anti-cancer drug-induced cancer cell apoptosis, which is an important downstream target of ROS. Zhu et al reported that apoptosis is induced in non-small cell lung cancer cells via the ROS-mediated ER stress pathway [17]. Moreover, Liu et al demonstrated that shikonin triggers cell apoptosis via the ROS-induced activation of the ER stress pathway [33].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that ROS accumulation in various types of cancers involves cell apoptosis and autophagy induced by anti-tumor drugs [13,14]. Increasing evidence suggests that ROS-mediated ER stress activation is involved in anti-cancer drug-induced apoptosis of cancer cells [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced intracellular ROS level, C/EBP-homologous protein, expression levels of glucose-regulated protein (GRP)78 Activated transcription factor 6 and caspase 12 Activated the inositol-requiring enzyme 1alpha and phosphorylation levels of protein kinase R-like ER kinase (Zhu et al, 2019).…”
Section: Lung Cancermentioning
confidence: 99%